Examining priority setting and resource allocation practices in county hospitals in Kenya - Barasa, Edwine W (Health Economics Unit, 2015)
Hospitals consume a significant proportion of healthcare budgets and are a key avenue for the delivery of key interventions. Understanding how hospitals use resources is therefore an important question. Priority setting research has however focused on the macro (national) and micro (patient) level, and neglected the meso (organizational, hospital) level practices. There is also a dearth of literature on priority setting in developing country hospitals, although they are recognized to suffer severe resource scarcity. This thesis describes and evaluates priority setting practices in Kenyan hospitals and identifies strategies for improvement. METHODOLOGY: A case study approach was used, where two public hospitals in coastal Kenya were selected as cases and three priority setting processes examined as nested cases. Data were collected over a seven month fieldwork period using in - depth interviews, document reviews, and non - participant observations. A modified thematic approach was used for data analysis. FINDINGS: Hospitals exhibit properties of complex adaptive systems (CASs) that exist in a dynamic state with multiple interacting agents. Weaknesses in the system hardware (resource scarcity) and software (tangible - guidelines and procedure s and intangible - leadership and actor relationships) led to the emergence of undesired properties. Both hospitals had comparable system hardware and tangible software, but differences in intangible software contributed to variations in priority setting practices. For example, good leadership and actor relations in one hospital lead to better inclusion of stakeholders and perceptions of fairness while weak leadership, heightened tensions among actors and less inclusive processes in the other hospital lead to distrust and perceptions of unfairness. RECOMMENDATIONS: The capacity of hospitals to set priorities should be improved across the interacting aspects of organizational hardware, and tangible and intangible software. Interventions should however recognize that hospitals are CASs. Rather than rectifying isolated aspects of the system, they should endeavor to create conditions for productive emergence.